2012
DOI: 10.1021/jf3036963
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Accumulation and Characterization of cDNAs Encoding Lumazine Synthase and Riboflavin Synthase in Bitter Melon (Momordica charantia)

Abstract: Riboflavin (vitamin B2) is the universal precursor of the coenzymes flavin mononucleotide and flavin adenine dinucleotide--cofactors that are essential for the activity of a wide variety of metabolic enzymes in animals, plants, and microbes. Using the RACE PCR approach, cDNAs encoding lumazine synthase (McLS) and riboflavin synthase (McRS), which catalyze the last two steps in the riboflavin biosynthetic pathway, were cloned from bitter melon (Momordica charantia), a popular vegetable crop in Asia. Amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, the four riboflavin biosynthetic genes showed significantly higher expression in the red fruits than in the green fruits; however, red fruits did not show higher accumulation of riboflavin content than green fruits. In our previous study, we also found that the transcription levels of riboflavin biosynthetic genes were not correlated with the accumulation of riboflavin in different tissues of Momordica charantia [13]. We hypothesize that there are several isoforms of riboflavin biosynthetic genes which have tissue-specific expression in plants.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, the four riboflavin biosynthetic genes showed significantly higher expression in the red fruits than in the green fruits; however, red fruits did not show higher accumulation of riboflavin content than green fruits. In our previous study, we also found that the transcription levels of riboflavin biosynthetic genes were not correlated with the accumulation of riboflavin in different tissues of Momordica charantia [13]. We hypothesize that there are several isoforms of riboflavin biosynthetic genes which have tissue-specific expression in plants.…”
Section: Resultsmentioning
confidence: 86%
“…The final step of the riboflavin biosynthetic pathway is mediated by riboflavin synthase (RS), which catalyzes the disproportionation of 6,7-dimethyl-8-ribityllumazine, affording riboflavin and 5-amino-6-ribitylamino-2,4(1 H ,3 H )-pyrimidinedione, which is recycled in the biosynthetic pathway [11]. Over the past 15 years, several researchers have investigated riboflavin biosynthesis by cloning a bifunctional protein with GCHYII and DHBP in Arabidopsis [9]; characterization of LS and RS has been conducted in spinach, tobacco, and bitter melon [12,13]. Recently, the availability of next-generation sequencing technologies has allowed the extensive investigation of the genes related to the riboflavin biosynthetic pathway in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Riboflavin is an essential vitamin in human nutrition occurring in a wide variety of food products, and it is produced biotechnologically and used in vitamin enriched food and food supplements. [1][2][3][4] Additionally, riboflavin is an important biological redox cofactor that can act as the universal precursor of the flavin adenine dinucleotide and coenzyme flavin mononucleotide. 5 In view of this, riboflavin is indispensable for the activity of a wide variety of metabolic enzymes in microbes, plants and animals, and it is very important for human and animal health.…”
Section: Introductionmentioning
confidence: 99%